Avaliacão de uma biorretenção como estrutura sustentável de drenagem urbana - Daniel Junior, Jair João (2013)
With the increase of waterproofing in urban centers, mainly generated by urbanization, it is necessary to search for new sustainable structures that act not only quantitative control, but also in the qualitative part of the rainwater. The little infiltration in urban areas, turns out to contributes to the contamination of water bodies, since the waters emanating from the runoff tends to "wash" the streets and sidewalks dragging pollutants found there until receiving bodies, this first part of the rain is known as the first flush. As an example of this type of structure, we have infiltration trenches, evaporation, mixed permeable pavements, as well as detention tanks and other. In Brazil there are not many studies that can provide accurate about sizing and functioning of these structures over the long term. Therefore, a bioretention or mixed trench (evapotranspiration and infiltration) was constructed on the campus of the Federal University of Santa Maria, and monitored from January 2011 until the month of March 2013 The main objective of this study is to evaluate the ability of the trench in quality control of effluents drained of a catchment area (roof), as well as the ability of the structure to treat the first flush originating from the roof. The quantitative monitoring revealed that the structure had a good performance in all events of the monitoring period, where the maximum level recorded was 80 cm, while the useful level of the structure is 1.20 m. The analysis of the colmatation, revealed a decrease in infiltration rate from the beginning until the end of the survey, showing the occurrence of the process of colmatation in the structure. The qualitative evaluation showed that the top layer does not have sufficient capacity to filter the effluent in the patterns requested. The coliform analysis, showed absence for total coliform and E colli on analyzes of the plants. Based on the results obtained in this study, it can be said that the trench mixed emerges as an effective alternative in the treatment quality / quantity of stormwater effluent when properly sized and operated.